The Lancet: an archive of surgical history - Frampton, S; Kneebone, R (Elsevier, 2023)
From the first days of The Lancet 200 years ago, surgery has had a central role in its existence. The journal has acted as a nerve centre, linking surgical innovation by individuals with challenge and debate in the wider profession. Such innovation shapes and is shaped by the social and political context of its time. Looking back over two centuries, the journal's many research articles, letters, and commentaries relating to surgery provide an invaluable insight that goes far beyond specific discoveries or breakthroughs.